An Efficient Catalytic Method for Regioselective Sulfenylation of Electron‐Rich Aza‐Aromatics at Room Temperature1. Issue 1 (19th November 2012) - Marcantoni, Enrico; Cipolletti, Roberto; Marsili, Laura; Menichetti, Stefano; Properzi, Roberta; Viglianisi, Caterina
Abstract: Electron‐rich aza‐aromatic compounds such as indoles and pyrroles are structures of particular interest and importance in organic chemistry. A useful methodology for the regioselective introduction of the sulfenyl group into electron‐rich aza‐aromatics using S ‐alkyl‐ and S ‐arylthiophthalimides as sulfenylating agents is described. Catalytic amounts of CeCl3 · 7H2 O/NaI are crucial to the promotion of this regioselective carbon–sulfur‐bond‐forming electrophilic aromatic substitution reaction. The reaction occurred under mild conditions, and the products were obtained in good to excellent yields. The method represents an efficient preparation of sulfenyl aza‐aromatics, which are useful intermediates for important organic transformations, due to the great importance of functionalized indoles among natural compounds and pharmaceutical products. Abstract : A useful method for the regioselective introduction of the sulfenyl group into electron‐rich aza‐aromatics using S ‐alkyl‐ and S ‐arylthiophthalimides as sulfenylating agents is described. Catalytic amounts of CeCl3 · 7H2 O/NaI are crucial to the promotion of this regioselective carbon–sulfur‐bond‐forming electrophilic aromatic substitution reaction.